2013
DOI: 10.1371/journal.pone.0072536
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Relationships between Rhynchosporium lolii sp. nov. and Other Rhynchosporium Species on Grasses

Abstract: The fungal genus Rhynchosporium (causative agent of leaf blotch) contains several host-specialised species, including R. commune (colonising barley and brome-grass), R. agropyri (couch-grass), R. secalis (rye and triticale) and the more distantly related R. orthosporum (cocksfoot). This study used molecular fingerprinting, multilocus DNA sequence data, conidial morphology, host range tests and scanning electron microscopy to investigate the relationship between Rhynchosporium species on ryegrasses, both econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…The genes of R. commune and R. secalis are highly similar lacking any introns, whereas an intron is present in the 28S gene of R. agropyri . The CCG species R. orthosporum and the recently described R. lolii [16] carry two introns of the same size in the 18S gene and single introns differing in length by one nucleotide in the 28S gene. The latter are homologous to the 28S intron of R. agropyri and located at the same site, but their sequences are 99 bp and 87 bp shorter at the 5′ and the 3′ side, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The genes of R. commune and R. secalis are highly similar lacking any introns, whereas an intron is present in the 28S gene of R. agropyri . The CCG species R. orthosporum and the recently described R. lolii [16] carry two introns of the same size in the 18S gene and single introns differing in length by one nucleotide in the 28S gene. The latter are homologous to the 28S intron of R. agropyri and located at the same site, but their sequences are 99 bp and 87 bp shorter at the 5′ and the 3′ side, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Agropyron repens ). Finally, fungal isolates from perennial ryegrass ( Lolium perenne ) were found to represent yet another species, R. lolii [16]. The cylindrical shape of the spores as well as phylogenetic analysis based on nucleic acid sequences position the latter species closer to R. orthosporum (cylindrical conidia group, CCG) than to the other three species (beaked conidia group, BCG).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The barley-infecting pathogen has been renamed Rhynchosporium commune . Recent taxonomic studies have shown that Rhynchosporium commune is a complex of four closely related Rhynchosporium species [ 9 ]. The assay has not yet been tested against the other Rhynchosporium species on other hosts.…”
Section: Notesmentioning
confidence: 99%